Advances in Signal Processing and Intelligent Recognition Systems Proceedings of Third International Symposium on Signal Processing and Intelligent Recognition Systems (SIRS-2017), September 13-16, 2017, Manipal, India - Thampi, Sabu M.; Krishnan, Sri.; Corchado Rodriguez, Juan Manuel; Das, Swagatam; Wozniak, Michal; Al-Jumeily, Dhiya; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This Edited Volume gathers a selection of refereed and revised papers originally presented at the Third International Symposium on Signal Processing and Intelligent Recognition Systems (SIRS'17), held on September 13-16, 2017 in Manipal, India. The papers offer stimulating insights into biometrics, digital watermarking, recognition systems, image and video processing, signal and speech processing, pattern recognition, machine learning and knowledge-based systems. Taken together, they offer a valuable resource for all researchers and scientists engaged in the various fields of signal processing and related areas.
Keywords: Computational intelligence; Signal processing; Artificial intelligence; Computational Intelligence; Signal, Speech and Image Processing; Artificial Intelligence